Helicobacter canis: A Review of Microbiological and Clinical Features - Lardinois, Benjamin; Belkhir, Leïla; Verroken, Alexia (Frontiers in Microbiology, 2022)
Helicobacter canis, an enterohepatic Helicobacter has proven its role in human diseases and has been rediscussed in recent years as its zoonotic potential is increasingly described. Routine microbiological detection of this pathogen is a difficult task as its culture may fail due to fastidious growth. It is therefore supposed that many clinical laboratories under-recognize H. canis infections. A review of all clinical and microbiological literature currently available from previous relevant H. canis human clinical cases, mainly bacteremias, added of a clinical case observed at the Cliniques universitaires Saint-Luc was performed. Clinical features of H. canis reports show the presence of underlying clinical conditions in 89% of the cases, bacteremia in 83%, associated fever in 58% and recent close contact with pets in 83%, especially dogs. The observed microbiological trends from 10 cases of bacteremias were a median of 4 days until positive blood culture bottle detection, subcultures showing a thin layer of small colonies under microaerophilic atmosphere at 35-42°C after 3 to 4 days of growing then an identification requiring 16S rRNA sequencing given the difficulties observed with MALDI-TOF MS. Low MICs were observed for penicillins, amoxicillin/clavulanic acid, carbapenems and metronidazole in opposite to high MIC for ciprofloxacin. A frequent association of H. canis with bacteremia in immunocompromised patients with recurrent fever in contact with pets, especially dogs, was identified. Considering the fastidious growing capacities, definitive identification from blood cultures may not be expected before 7 days. Intravenous ceftriaxone, oral doxycycline or metronidazole have been suggested as efficient therapeutic choices.